Functional antibody responses to SARS-CoV-2 variants before and after booster vaccination among adults in Ghana - F. D. Partey; A. N. A. Pobee; I. K. Damptey; F. Osei; M. M. A. K. Owusu-Amponsah; Y. A. A. Ansah; C. Ye; S. Bradfute; I. Hurwitz; P. K. Quashie; M. F. Ofori; A. K. Kusi; et al. (Experimental Biology and Medicine)
COVID-19 booster vaccinations are needed to enhance waning immunity and the emergence of new variants. In Africa, where COVID-19 vaccine coverage is low, there is a paucity of data on COVID-19 vaccine-induced immunity, particularly in the post-omicron era. This study examined the functional activity of vaccine-induced antibody responses against different variants before and after booster vaccinations in adults in Ghana, between November 2022 and February 2023. SARS-CoV-2 nucleocapsid protein and spike receptor binding domain (RBD) antigen-specific IgG levels against different viral variants were determined in plasma. Plasma was tested for the ability to inhibit ACE-2 binding to RBD variants. N antigen-specific antibody levels were comparable between vaccinated and previously infected, but unvaccinated individuals. However, RBD IgG levels before booster vaccinations were significantly higher in vaccinated participants than in exposed, unvaccinated individuals, except for Omicron. RBD IgG levels remained unchanged after the booster in participants with three prior vaccine doses but were significantly higher than in those with only primary vaccinations (Wild type p = 0.0315, Alpha p = 0.0090, Beta p = 0.0020, Delta p = 0.0040) except Omicron (p = 0.09). Participants who received the Pfizer-BioNTech vaccine showed a significant increase (p < 0.05) in RBD IgG levels against all tested variants from baseline to 3 months. In contrast, participants who received the J&J vaccine only showed a significant increase in RBD IgG to Wildtype (p = 0.04), Alpha (p < 0.0001), and Beta (p < 0.0001), but not Delta and Omicron. The inhibition of ACE-2 binding and live virus neutralization titers were significantly higher in vaccinated individuals than in unvaccinated individuals before the booster (p < 0.001). Virus neutralization titers against Wildtype were significantly high 3 months after booster (p < 0.001), but neutralization titers against Omicron remained stable from baseline to 3 months after booster. Extended interval between vaccinations may enhance vaccine-induced antibody responses.